Why thinking aloud matters for usability evaluation? - Abu Seman, Esmadi Abu; Hussein, Idyawati; Mahmud, Murni (2010)
Computer application should be enjoyable to use, do useful things and enhance the lives of people who use them. In the days of the web, issues of usability are critical to computer application such as e-commerce. Usability is re-defined as trade-off between increasing the user's motivation to encourage exploration and purchasing in e-commerce, and the costs of usability errors. This study reports on methodology applying expert-based and think-aloud methods in the laboratory setting. Usability evaluation of two airlines websites was carried out to study user performance and to investigate the websites' conformance with ISO standards. Subjects comprised actual users who had experience using the online booking applications. Despite having results indicated that usability evaluation not only reliable in rating a computer application that is enjoyable and usable; it discovered design elements that manipulate users to make mistakes.